Performance Analysis of Electric Bicycles with Planetary BLDC Motors under Different Rider Weights - Persada, Hegen; Dalimunthe, Ernando Rizki; Trisnawati, Fika; Putri, Novia Utami (Fakultas Teknik Universitas Bhayangkara, 2025)
Electric bicycles are increasingly used as eco-friendly personal transportation due to their efficiency and low emissions. This study analyzes the effect of rider weight on the energy consumption of a 48V 14Ah lithium-ion battery in an electric bicycle equipped with a 500W planetary BLDC motor. Tests were carried out on three rider weight categories: 60–65 kg, 70–75 kg, and 80–85 kg, to evaluate their impact on current consumption, travel distance, and operating duration. Measurements were taken using a PZEM-015 sensor to monitor voltage, current, and battery capacity in real-time, while speed and distance data were recorded through the Strava application. The results show that as the rider’s weight increases, the average current consumption also rises, decreasing both distance and travel time in a nearly linear pattern. At 60 kg, the bicycle traveled 24.32 km with an average current of 9.52 A, while at 80 kg, the distance decreased to 19.76 km with an average current of 23.15 A. The findings indicate that rider weight significantly affects electric bicycles' performance and energy efficiency. Heavier riders require greater battery power, shorter travel range, and reduced operational efficiency.